Análisis jurídico y doctrinario del empleo de las armas no letales en la legislación ecuatoriana en lo que respecta al uso de las armas electrochoques en el ejercicio de sus funciones de la Policía Nacional en servicio activo - Tene Fernández, Jhonnan Vicente (2024)
The research paper titled "Legal and doctrinal analysis of the use of non-lethal weapons in ecuadorian legislation regarding the use of electroshock weapons by the National Police in active service" aims to study the feasibility of expanding and implementing electroshock weapons as non-lethal weapons by the National Police of Ecuador, as this prestigious institution must maintain peace, order, and public security in the country. Non-lethal weapons, known for not causing death, have been developed alongside technological advancements to replace lethal weapons. In Ecuador, electroshock weapons are mentioned in the Regulation for the Legal, Appropriate, and Proportional Use of Force by the National Police, but they are not precisely defined, and there is no instruction manual establishing their correct use. Therefore, it is important to consider and analyze expanding the use of electroshock weapons beyond what the law currently allows, similar to foreign legislation in countries such as Argentina, Spain, and Australia. This research aims to conduct a legal, doctrinal, and comparative study of the use of non-lethal weapons, specifically electroshock weapons, determining the situations for their use and limitations to combat the increasing crime rate in the country.